CARBON STOCK DUE TO THE INTENSITY OF THE USE OF FOREST AREAS IN FOREST MANAGEMENT UNIT OF WEST BALI - Wiyanti, Wiyanti; Lanya, Indayati; Merit, I Nyoman; Antara, Made (International Journal of Biosciences and Biotechnology, 2016)
This study aimed to determine the magnitude of the changes in carbon stocks due to changes in forest utilisation. Location of the study include planted forests, coffee plantations, mix garden, and cajuput region. The method used in this study was to estimate carbon stock based on the weight of biomass both above the surface and underground. Measurements were made on the biomass of trees and undergrowth, necromass (dead plant parts), both woody and non-woody (litter), and reserve C in the soil. The results showed that there were considerable differences of carbon stock in each area utilisation. The highest carbon stock found in the mix garden (275.62 tonnes/ha), then decrease at mahogany forest (269.63 tonnes/ha), planted forests (231.45 tonnes/ha), old cajuput (Melaleuca cajuput) (118.53 tonnes/ha), trimmed cajuput (86.57 tonnes/ha), coffee plantations (74.37 tonnes/ha), and un-trimmed cajuput (56.78 tonnes/ha). The recommendation can draw out in this research are: ( 1 ) In the area of coffee planting, horticultural forestry can be developed in the form of rows of plants among the coffee plants and ( 2 ) cajuput planting can be done with the system surjan and each row of cajuput consists of 2 rows with a distance planting more tightly.
Keywords: carbon stock; forest area; biomass